2010
DOI: 10.5014/ajot.2010.09034
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mental Practice to Improve Upper-Limb Recovery After Stroke: A Systematic Review

Abstract: OBJECTIVE. We sought to determine whether mental practice is an effective intervention to improve upper-limb recovery after stroke. METHOD. We conducted a systematic review of the literature, searching electronic databases for the years 1985 to February 2009. We selected studies according to specified criteria, rated each study for level of evidence, and summarized study elements. RESULTS. Studies differed with respect to design, patient characteristics, intervention protocols, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 78 publications
2
86
0
3
Order By: Relevance
“…Inhibitory repetitive transcranial magnetic stimulation (rTMS – 1 Hz) over the unaffected primary motor cortex improves the timing of grasping and lifting with the affected hand (Dafotakis et al, 2008). Mirror therapy (Michielsen et al, 2011) and mental training have a positive effect on the hand function (Müller et al, 2007; Nilsen et al, 2010; Prasad et al, 2010; Ietswaart et al, 2011). Robot-assisted therapies also have potential for prehension recovery (Ziherl et al, 2010; Merians et al, 2011).…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…Inhibitory repetitive transcranial magnetic stimulation (rTMS – 1 Hz) over the unaffected primary motor cortex improves the timing of grasping and lifting with the affected hand (Dafotakis et al, 2008). Mirror therapy (Michielsen et al, 2011) and mental training have a positive effect on the hand function (Müller et al, 2007; Nilsen et al, 2010; Prasad et al, 2010; Ietswaart et al, 2011). Robot-assisted therapies also have potential for prehension recovery (Ziherl et al, 2010; Merians et al, 2011).…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…Its purpose is similar to that of physical practice (PP) in that it is performed for the purpose of learning or improving upon the performance of a physical activity (Jackson et al, 2001). Mental practice interventions post-stroke have shown promising results for functional improvement of motor skills (for review, refer to Nilsen, Gillen & Gordon, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…And mental practice (MP) is a training method during which a person cognitively rehearses a physical skill using MI in the absence of overt, physical movements for the purpose of enhancing motor skill performance [7]. Recently, research has shown that MP using MI (MP_MI) combined with physical practice (PP) can promote recovery of motor function [810].…”
Section: Introductionmentioning
confidence: 99%